Inflammation, coronary plaque progression, and statin use: A secondary analysis of the Risk Stratification with Image Guidance of HMG CoA Reductase Inhibitor Therapy (RIGHT) study. Issue 6 (2nd April 2022) - Scott, Colin; Lateef, Sundus S.; Hong, Christin G.; Dey, Amit K.; Manyak, Grigory A.; Patel, Nidhi H.; Zhou, Wunan; Sorokin, Alexander V.; Abdelrahman, Khaled; Uceda, Domingo; Teklu, Meron; Wu, Colin; et al.
Abstract: Background: Statin treatment is a potent lipid‐lowering therapy associated with decreased cardiovascular risk and mortality. Recent studies including the PARADIGM trial have demonstrated the impact of statins on promoting calcified coronary plaque. Hypothesis: The degree of systemic inflammation impacts the amount of increase in coronary plaque calcification over 2 years of statin treatment. Methods: A subgroup of 142 participants was analyzed from the Risk Stratification with Image Guidance of HMG CoA Reductase Inhibitor Therapy (RIGHT) study (NCT01212900), who were on statin treatment and underwent cardiac computed tomography angiography (CCTA) at baseline and 2‐year follow‐up. This cohort was stratified by baseline median levels of high‐sensitivity hs‐CRP and analyzed with linear regressions using Stata‐17 (StataCorp). Results: In the high versus low hs‐CRP group, patients with higher baseline median hs‐CRP had increased BMI (median [IQR]; 29 [27–31] vs. 27 [24–28]; p < .001), hypertension (59% vs. 41%; p = .03), and LDL‐C levels (97 [77–113] vs. 87 [75–97] mg/dl; p = .01). After 2 years of statin treatment, the high hs‐CRP group had significant increase in dense‐calcified coronary burden versus the low hs‐CRP group (1.27 vs. 0.32 mm 2 [100×]; p = .02), beyond adjustment ( β = .2; p = .03). Conclusions: Statin treatment over 2 years associated with a significant increase in coronary calcification in patients with higher systemic inflammation, as measured by hs‐CRP. These findings suggest that systemic inflammation plays a role in coronary calcification and further studies should be performed to better elucidate these findings.